Nationalism and patriotism in the work of Antonio Machado - De Blas Guerrero, Andrés (Historia y Política, 2018)
The unquestionable political signification of Antonio Machado’s literary work has not been accompanied by parallel scholarly attention to this dimension of his writing. The copious bibliography on Machado has not abounded in reflections on the political aspects of his work comparable to considerations of its literary, philosophical or even religious features. This observation is also applicable to the topic of patriotism and nationalism. The remarkable political influence that Antonio Machado exerted during the period of the Second Republic and, especially, the Spanish Civil War, and his significance as an anti-Francoist symbol throughout the Dictatorship must not conceal the fact that Machado’s political preparation and the resultant consistency of his political worldview were not characterized by their soundness.